Developing a core outcome set for assessing interventions and care for parents after neonatal death in high-income countries (iCHOOSE Neonatal study): protocol for a mixed-methods study - James Webbe; Mehali Patel; Danya Bakhbakhi; Christy Burden; Mary Lynch; Laura Timlin; Lisa Hinton; Abigail Fraser; Anna Davies; Maggie Redshaw; David Odd; Charlotte Williams; et al. (BMJ Open)
Introduction Neonatal death exerts long-lasting impact on parents’ mental health, finances and relationships, and the wider family. There is national and international momentum to evaluate interventions to support parents after the death of a baby. Core Outcome Sets (COSs) provide a minimum set of outcomes, agreed by stakeholders to be important, which should be evaluated in all studies to support evidence syntheses and identification of the most effective interventions. We aim to develop a COS for assessing interventions and care after neonatal death in high-income countries, to support future evidence syntheses and enable the identification of effective interventions and care for parents.Methods and analysis We will develop the COS in six phases. A parent involvement group and stakeholder steering committee have been established and have informed each planned phase: (1) systematic review of quantitative studies evaluating care and interventions provided after neonatal death, to describe interventions, outcomes and outcome measurement tools used to assess intervention effectiveness; (2) qualitative interviews with parents who have experienced neonatal death to identify outcomes important and relevant to them; (3) think-aloud interviews with stakeholders (bereaved parents, healthcare professionals and other stakeholders) to develop and refine an online survey; (4) real-time online international Delphi survey with bereaved parents, healthcare professionals and other stakeholders to shortlist outcomes for consideration in the COS; (5) adapted nominal group online consensus meetings with parents, healthcare professionals and other stakeholders to agree final COS and (6) identification of a preliminary set of measurement tools.Ethics and dissemination Ethical approval has been granted for all activities to be undertaken by the University of Bristol Health Sciences Faculty Research Ethics Committee (reference: 15121). We will disseminate the findings via peer-reviewed publications and relevant academic and professional conferences.PROSPERO registration number CRD42020151365.